Retinal and retinol are potential regulators of gene expression in the keratinocyte cell line HaCaT - Amann, Philipp M.; Schadendorf, Dirk; Owen, Robert; Korn, Bernhard; Eichmüller, Stefan B.; Bazhin, Alexandr V. (Experimental dermatology, 2011)
Please cite this paper as: Retinal and retinol are potential regulators of gene expression in the keratinocyte cell line HaCaT. Experimental Dermatology 2010. Abstract: Vitamin A is a pivotal regulator of differentiation and growth of developing and adult skin. Retinoic acid is the major physiologically active form of vitamin A regulating the expression of different genes through retinoic acid nuclear receptors. Here, we present evidence that other vitamin A derivates - retinol and retinal - are also capable of functioning as regulators of gene expression in the keratinocyte cell line HaCaT. We have shown that all-trans retinol (ATRol) and all-trans retinal (ATRal) are capable of modulating gene expression in keratinocytes, which is not because of vitamin A metabolism in the cells, and retinol and retinal modulate gene expression through nuclear receptors: retinoic acid receptors (RARs) and retinoid X receptors (RXRs). Based on the data, we propose that ATRol and all-trans retinal, in addition to all-trans retinoic acid, can function as important regulators of gene expression manifesting their effect through the nuclear receptors RARs and RXRs.